Kajian Sistem Penyaliran Tambang Bawah Tanah Pada PT Allied Indo Coal Jaya Sawahlunto Sumatera Barat - Ferdinand De Lessep Samosir; Franto Franto; Delita Ega Andini (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2021)
PT Allied Inco Coal Jaya (PT. AICJ) is a company that work in coal mining industry. This research is done at underground mining located at main shaft tunnel at +347 metres above mean sea level (MASL) with 334,04 m in length with room and pillar method as its mining method. This research is using quantitative method. From the calculation obtained, the total of incoming water into the mining production area is 6.13 m3/hour. For the actual incoming from well is as much as 13.32 m3/hour with the total head is as big as 29.56 m, as the time needed to discharge is 6.45 hour. Making the dewatering layout design for the incoming water at elevation of +347.32 MASL to main sump at +318 MASL with total length of 201.6 m, while the water discharged at continuous pumping at elevation +306 MASL moving toward +347.43 MASL with total distance 341.32 m. with the addition to incoming water there is an increase in the pumping working hours so it is concluded that there is difference between the planned cost and actual cost of Rp. 832,269.96.